2010
DOI: 10.1021/jo101704b
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Telcagepant, a CGRP Receptor Antagonist for the Treatment of Migraine

Abstract: A highly efficient, asymmetric synthesis of telcagepant (1), a CGRP receptor antagonist for the treatment of migraine, is described. This synthesis features the first application of iminium organocatalysis on an industrial scale. The key to the success of this organocatalytic transformation was the identification of a dual acid cocatalyst system, which allowed striking a balance of the reaction efficiency and product stability effectively. As such, via an iminium species, the necessnary C-6 stereogenicity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 52 publications
1
50
0
Order By: Relevance
“…For example, β -fluoroalkylamines are less basic than their hydrocarbon counterparts (p K a H 10.7 versus 5.7 for ethylamine and trifluoroethylamine respectively)27 and often exhibit decreased acute toxicity and increased metabolic stability rendering them very attractive in pharmaceutical contexts (for examples, see Fig. 1b)2829303132. Unfortunately, while many C–H trifluoroethylation methods have been reported333435363738, there are fewer reagents for the trifluoroethylation of amines (Fig.…”
mentioning
confidence: 99%
“…For example, β -fluoroalkylamines are less basic than their hydrocarbon counterparts (p K a H 10.7 versus 5.7 for ethylamine and trifluoroethylamine respectively)27 and often exhibit decreased acute toxicity and increased metabolic stability rendering them very attractive in pharmaceutical contexts (for examples, see Fig. 1b)2829303132. Unfortunately, while many C–H trifluoroethylation methods have been reported333435363738, there are fewer reagents for the trifluoroethylation of amines (Fig.…”
mentioning
confidence: 99%
“…As previous studies indicated that alcohols or THF/H 2 O are suitable solvents for the asymmetric Michael reaction of nitroalkane, we investigated solvents such as MeOH, i PrOH and THF/H 2 O (Table , entries 1, 2, 3) and found that i PrOH was suitable. The ratio of nitroalkane 3 and cinnamaldehyde 4b was then examined, which revealed that an excess of nitroalkane gave better yield (entries 3, 4, 5, 6).…”
Section: Resultsmentioning
confidence: 99%
“…To this end, an organocatalytic approach, namely, an iminium ion catalysed conjugate addition of nitromethane to a proper cinnamaldehyde [113], was judged as more promising than other asymmetric preparations based on transition metal catalysed reactions, such as ruthenium-catalysed hydrogenation [114] and rhodium based Hayashi-Miyaura addition [115]. Although previously reported with related substrates [116, 117] the organocatalytic step required a careful optimisation for its large scale implementation, as the formation of several by-products was observed under the reported conditions.…”
Section: Discussionmentioning
confidence: 99%